A Study on the Age Range of Puberty of Swamp Buffalo Heifers under an Integrated Farming System in Eastern Thailand - Chaikhun-Marcou, Thuchadaporn; Suebkhampet, Araya (Journal of Mahanakorn Veterinary Medicine, 2024)
Recently, in Thailand, some swamp buffalo breeders have been developing an integrated farming system that incorporates concentrate supplementation, stress-reducing management practices, insemination with proven high-performance bulls and systematic data recording. To facilitate and optimize this process, this study aimed to determine the appropriate age for puberty and reproduction in young swamp buffaloes. Twenty-five swamp buffaloes from six breeder farms in Eastern Thailand were muti-stage sampling selected. The animals were divided into four age groups based on their birthdate records: Group I (18-23 months), Group II (24-29 months), Group III (30-35 months) and Group IV (36 months and older). Physical examinations, including body condition score, body weight and measurements of the pin bone and hook bone, as well as breeding soundness evaluations (including cervical diameter, ovarian structures and progesterone levels), were conducted over a 14-day interval. Cycling buffaloes were identified by a progesterone level (P4) of ≥1 ng/ml at least once during the study period. Statistical analysis of the number of cycling buffaloes in each group revealed that the optimal puberty period for suitable reproduction in swamp buffalo heifers occurred in Group II (24-29 months), with a statistically significant difference noted (P<0.01). However, no statistically significant differences were observed among the groups regarding physical and breeding soundness parameters. This information on reducing the appropriate puberty age for swamp buffalo raised under an integrated farming system may assist in establishing guidelines for breeding programs (utilizing proven bull semen), improving farm management (through concentrate supplementation) and enhancing the lifespan and productivity of buffaloes.